Functional Ecology of a Blue Light Photoreceptor: Effects of Phototropin-1 on Root Growth Enhance Drought Tolerance in Arabidopsis thaliana - Galen, Candace (The New Phytologist, 2007)
• The blue light photoreceptor phototropin-1 has been shown to enhance fitness in Arabidosis thaliana under field conditions. Here, we ask whether performance consequences of phototropin-1 reflect its impact on root growth and drought tolerance. • We used a PHOT1-GFP gene construct to test whether phototropin-1 abundance in roots is highest at shallow soil depths where light penetration is greatest. We then compared root growth efficiency and size at maturity between individuals with and without functional phototropin-1. Comparisons were made under wet and dry conditions to assess the impact of phototropin-1 on drought tolerance. • Phototropin-1 was most abundant in upper root regions and its impact on root growth efficiency decreased with soil depth. Roots of plants with functional phototropin-1 made fewer random turns and traveled further for a given length (higher efficiency) than roots of phot1 mutants. In dry (but not wet) soil, enhancement of root growth efficiency by phototropin-1 increased plant size at maturity. • Results indicate that phototropin-1 enhances performance under drought by mediating plastic increases in root growth efficiency near the soil surface.